Prospects of implant with locking plate in fixation of subtrochanteric fracture: experimental demonstration of its potential benefits on synthetic femur model with supportive hierarchical nonlinear hyperelastic finite element analysis - Latifi, Mohammed Hadi; Ganthel, Kunalan; Rukmanikanthan, Shanmugam; Mansor, Azura; Kamarul, Tunku; Bilgen, Mehmet (BMC, 2012)
Background: Effective fixation of fracture requires careful selection of a suitable implant to provide stability and durability. Implant with a feature of locking plate (LP) has been used widely for treating distal fractures in femur because of its favourable clinical outcome, but its potential in fixing proximal fractures in the subtrochancteric region has yet to be explored. Therefore, this comparative study was undertaken to demonstrate the merits of the LP implant in treating the subtrochancteric fractures by comparing its performance limits against those obtained with the more traditional implants; angle blade plate (ABP) and dynamic condylar screw plate (DCSP). Materials and Methods: Nine standard composite femurs were acquired, divided into three groups and fixed with LP (n=3), ABP (n=3)and DCSP (n=3). The fracture was modeled by a 20 mm gap created at the subtrochanteric region to experimentally study the biomechanical responses of the implants under axial static and dynamic loading paradigms. To confirm the experimental findings and to understand the critical interactions at the boundaries, the synthetic femur/implant systems were numerically analyzed by constructing hierarchical finite element models with nonlinear hyperelastic properties. The predictions from the analyses were then compared against the experimental measurements to demonstrate the validity of the numeric model, and to characterize the internal load distribution in the femur and load bearing properties of each implant. Results: The average measurements indicated that the constructs with ABP, DCPS and LP respectively had overall stiffness values of 70.9, 110.2 and 131.4 N/mm, and exhibited reversible deformations of 12.4, 4.9 and 4.1 mm and plastic deformations of 11.3, 2.4 and 1.4 mm at the applied dynamic loads of 400 N and 1000 N. The corresponding peak cyclic load to failure was 1100, 1167 and 1600 N. The errors between the displacements measured experimentally or predicted by the nonlinear hierarchical hyperelastic model were less than 18 . In the implanted femur heads, the principal stresses were spatially heterogeneous for ABP and DCSP but more homogenous for LP, meaning lower the stress concentrations. Conclusion: When fixed with the implant augmented with LP, the synthetic femur model of subtrochancteric fracture consistently exceeds in the key biomechanical measures of stability and durability. This capability makes the LP impant potentially a viable alternative to conventional ABP or DCSP for the clinical treatment of the subtrochancteric femur fracture.